Phenotype-genotype correlation and treatment outcomes in mevalonate kinase deficiency: A large Turkish cohort - Kaplan, Melike Mehves; Tekin, Zahide Ekici; Konte, Elif Kilic; Balik, Zeynep; Aydin, Tuncay; Caglayan, Sengul; Acar, Banu Celikel (W B Saunders Co-Elsevier Inc, 2026)
Objectives: This study aimed to comprehensively assess the clinical spectrum, genotype-phenotype correlations, and treatment responses in a large cohort of Turkish pediatric patients with genetically confirmed mevalonate kinase deficiency (MKD). Methods: This retrospective, multicenter cohort study included 107 genetically confirmed MKD patients followed between 2010 and 2024 across 25 pediatric rheumatology centers in Turkey. Demographic characteristics, clinical features, laboratory parameters, genotypic data, and treatment outcomes were recorded and analyzed. Results: Of the 107 patients, 48 (44.9%) were female. The median age at symptom onset was 7 (3-24) months, and the median age at diagnosis was 71 (27-115) months. The most frequent clinical features included fever in adenopathy in 64 (59.8%), vomiting in 52 (48.6%), and oral aphthae in 50 (46.7%). Less frequent findings included pancreatitis in 2 (1.9%), genital aphthae in 2 (1.9%), neurosensory hearing loss in 3 (2.8%), and peutic agents. Anakinra yielded no clinical response in 14 (13.1%), partial response in 17 (15.9%), and complete response in 13 (12.1%) patients. Canakinumab treatment resulted in no response in 2 (1.9%) patients, partial and therapeutic outcomes. We also confirm that heterozygous individuals may express the disease phenotype.
Keywords: Mevalonate kinase deficiency; Phenotype; Genotype; IL-1 Antagonists; Treatment response